2016
DOI: 10.5588/ijtld.15.0497
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer awareness and anticipated delay before seeking medical help in the middle-belt population of Nigeria

Abstract: The awareness of lung cancer warning signs and risk factors are not satisfactory in Nigeria. There is a need to increase awareness about the condition to prevent delays in seeking medical help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…The main goal was to include studies from LMICs, whose findings demonstrated potentials for transferability and/or generalizability to settings in SSA. This scoping review identified 9 articles published between 2008 and 2018, eight of which recognized the level of lung cancer knowledge, risk factors and awareness of warning signs and symptoms in LMICs, mostly in Africa and Asia [20,[31][32][33][34][35][36][37]. Our findings demonstrated a gap in literature on individual and community level interventions promoting lung cancer awareness and palliative care in SSA specifically and LMICs generally.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main goal was to include studies from LMICs, whose findings demonstrated potentials for transferability and/or generalizability to settings in SSA. This scoping review identified 9 articles published between 2008 and 2018, eight of which recognized the level of lung cancer knowledge, risk factors and awareness of warning signs and symptoms in LMICs, mostly in Africa and Asia [20,[31][32][33][34][35][36][37]. Our findings demonstrated a gap in literature on individual and community level interventions promoting lung cancer awareness and palliative care in SSA specifically and LMICs generally.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were conducted in LMICs and published between 2008 and 2018, resulting in a total sample size of 3563 participants from primary studies. The majority of the participants were males in six studies [20,[31][32][33][34][35], two studies had a slight female preponderance [36,37], while one study [21] was a literature review. Of nine studies included, 6 were cross-sectional studies [31-34, 36, 37], one was a pre-test and post-test study design [35], one was a prospective study [20] and the last one was a literature review [21].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations